Effect of Sodium Ascorbate, Grape Seed Extract, and Aloe Vera Application after In-Office Bleaching on the Bond Strength of Enamel: A 3-Year Evaluation - Alexandra Mena-Serrano; Eliana Aldás Fierro; Ximena Estrada; Alejandra Boada; Michel Wendlinger; Michael Willian Favoreto; Alessandro D. Loguercio; Alessandra Reis (Hindawi Limited, 2023)
Introduction. Dental bleaching is the first choice to improve smile esthetics, but, in some cases, it needs to be associated with resin composite restoration to obtain a satisfactory result. Unfortunately, the bonding of resin-based materials can be impaired due to residual oxygen molecules, which can decrease the durability of the restoration. Objectives. To evaluate the effect of the antioxidant application on the bond strength of bleached enamel after 24 hr and 3 years of water storage. Methods. In total, 84 bovine teeth were used in this study. Of these, 77 were bleached with 35% hydrogen peroxide in a single session for three cycles of 15 min. Then, the specimens were divided into groups (n = 7 each): control (without bleaching), without antioxidant (WA) use; application of 10% sodium ascorbate (SA) gel, grape seed (GS) extract, and aloe vera (AV). The restorative procedure was performed immediately after bleaching, 7 and 14 days after bleaching. Specimens were sectioned and evaluated using microtensile bond strength (μTBS). Half of the resin-enamel sticks were tested after 24 hr, and the remaining half after 3 years of water storage. µTBS data were analyzed using a three-way analysis of variance, Tukey's test, and Dunnett's test. Results. The lowest µTBS values were observed when the restoration was performed immediately after bleaching in the AV, GS, and WA groups when compared with the SA group (p<0.005). However, no significant differences were observed among all groups after 3 years of water storage (p<0.001). Conclusions. SA at 10% was the most effective antioxidant agent for improving the immediate bond strength. However, independent of the antioxidant agent used, the bond strength values were maintained or recovered after 3 years of water storage. SA at 10% could be used to avoid delayed bonding procedures after in-office whitening without compromising bond strength over time. Clinical Significance. The use of antioxidants after dental bleaching can be effective in improving the bonding durability of the adhesive restorations.